(N-sec-Butyl-N-n-propyldithiocarbamato-kappa S-2,S `)triphenyltin(IV) - Awang, N.; Baba, I.; Yamin, B.M.; Ng, S.W.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
The Sn atom in the title compound, [Sn(C6H5)(3)(C8H16NS2)], is pentacoordinated by two S atoms, derived from an asymmetrically coordinating dithiocarbamate ligand, and three ipso-C atoms. The coordination geometry is intermediate between square-pyramidal and trigonal-bipyramidal, with a leaning towards the latter. The presence of close intramolecular C-H center dot center dot center dot S contacts preclude the S atoms from forming significant intermolecular interactions. Rather, molecules are consolidated in the crystal structure by C-H center dot center dot center dot pi interactions.